MAIN CHARACTERISTICS OF THE RISK MANAGEMENT MECHANISM IN MANUFACTURING ENTERPRISES - Muxitdinov, Shuxrat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Improvement of risk management mechanisms in production enterprises is of particular importance. Because risks are characterized by different levels of danger depending on the type. This article provides detailed information about risks in the management of production enterprises and their classification into types and levels when taking into account the amount of damage.